Will implementing pillar two measures hinder the rehabilitation of South African Mines? - Gouws, Janke (Department of Finance and Tax, 2025)
South Africa imposes rehabilitation obligations on mining right holders to address the damage caused by mining operations. The National Environmental Management Act, 17 of 1998 (“NEMA”) requires each mining right holder to make financial provision to cover their rehabilitation costs in the future. A rehabilitation trust is one of the allowable financial vehicles listed under NEMA for purposes of financial provisioning. The mining right holder funds the rehabilitation trust through contributions that the trust invests in. Under section 37A, read with section 10(1)(cP) of the South African Income Tax Act, 1962 (“ITA”), the mining right holder can deduct these contributions for income tax purposes. The rehabilitation trust is also granted a tax exemption for all receipts accruing to it. In December 2024, the Global Minimum Tax Act, 46 of 2024 (“GMT Act”) was enacted in South Africa to implement Pillar Two measures in South Africa. Pillar Two imposes a global minimum tax of 15 per cent on multinational entities with revenue of EUR750 million or more to prevent large multinationals from shifting their profits to low-taxed jurisdictions. The Global Anti-Base Erosion (“GloBE”) rules and commentary guide the calculations to determine the effective tax rate and resulting top-up tax payable in terms thereof. This dissertation evaluates whether imposing Pillar Two measures in South Africa would render rehabilitation trusts ineffective and inefficient due to the ITA tax incentive that may result in a lower GloBE effective tax rate, ultimately forcing mining groups to pay a top-up tax for rehabilitation compliance. The main finding of this dissertation is that rehabilitation trusts, as members of a multinational group (“MNE”) with revenue of EUR 750 million or more, will have their financials included in the mining group's effective tax rate calculation regarding Pillar Two. The tax incentive provided in the ITA could affect the calculation by lowering the mining group's effective tax rate to below 15 per cent, resulting in the payment of top-up taxes. The concern is that mining groups will be deterred from using rehabilitation trusts, which would abandon them and complicate their regulation, as the other vehicles are not as regulated. The solution presented in this dissertation is to include rehabilitation trusts as an excluded entity for purposes of Pillar Two, as they operate similarly to governmental entities.